2018
DOI: 10.1049/iet-net.2017.0137
|View full text |Cite
|
Sign up to set email alerts
|

Privacy issues in social networks and analysis: a comprehensive survey

Abstract: Social networks have become part of today's life; however, they also create numerous privacy problems for their users as they reveal sensitive information. Thus, the privacy preservation has become a big problem in social networks and there are several researches related to this topic. However, the current research achievements for this issue are only ad hoc solutions and the broad picture of the problem is not clear. This paper surveys a wide range of related researches and realises that the topic includes ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…Protecting the privacy of the individual user and his/her community, and enhancing the anonymous data utility is a longstanding challenge in SN users' data publishing [35]. According to the Pham et al [36] there are three major privacy areas in SN that are shown in Fig. 1.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Protecting the privacy of the individual user and his/her community, and enhancing the anonymous data utility is a longstanding challenge in SN users' data publishing [35]. According to the Pham et al [36] there are three major privacy areas in SN that are shown in Fig. 1.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Nevertheless, the share of part or full personal information [105,106], such as credit card numbers, could be stolen and used in illegal activities. That leads us to ask how edge computing could protect sensitive information, which imposes serious considerations related to the data security of citizens?…”
Section: Social Network Into Edge Computingmentioning
confidence: 99%
“…Since the risk has a devastating impact on the daily life of the people involved (for example, disclosure of sensitive data, such as e-mails, instant messages, or private relationships), protecting user privacy has become an important and challenging problem in online social networks. Anonymization of the social network structure [1], [2] is a common approach to protecting user privacy. A social network may be modeled as a graph, where vertices represent individuals, organizations or users, and edges represent connections, relationships between users or information flows [3].…”
Section: Introductionmentioning
confidence: 99%